1984 Olympics Track and Field Competition at Los Angeles Coliseum - Watkins, Howard::::::::: (1984)
Albert Watkins, Howard Watkins and Adam Watkins with track field behind them; fans exiting East end of Coliseum with lit torch, rings in background